Integrating culture into EFL teaching behind classroom doors: A case study of upper secondary teachers in Vietnam - Chau, Thi Hoang Hoa (H. : ĐHQGHN, 2019)
In the context of globalization, intercultural integration has gained a better position in teaching and learning English in Vietnam, even in general education. In fact, intercultural objectives and intercultural content have been added to the expected curriculum and pilot coursebooks for teaching English in upper secondary education. Prior to the implementation of the new curriculum, it is essential to explore how teachers deal with intercultural content provided in the coursebooks. From the view of intercultural teaching, this study focuses on the positionality of intercultural objectives and intercultural teaching strategies in teachers’ practice. Data collected from 101 teachers through questionnaire and six class observations illustrate that (1) teachers did not include intercultural objectives in EFL lessons and (2) they rarely conducted intercultural language activities in their teaching practice. It is recommended that intercultural education needs more attention from educational managers to support the EFL teachers in upper secondary schools to incorporate culture into their teaching more effectively, which contributes to the accomplishment of a reformed English curriculum objective – building comprehensive intercultural competence for the students